Pujawali Pura Dalem Tungkub Mengwitani Sebagai Inspirasi Penciptaan Karya Lukis - Prayoga, I Made Adi Putra; Setem, I Wayan; Yudha, I Made Bendi (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2024)
Pujawali is a day to celebrated by Hindus as a form of gratitude to God. Furthermore, the pujawali at Dalem Tungkub Mengwitani temple includes several processions, including the process of ngias sumpang, going to the purification, give the blabaran, mamendet, murwa daksina, joint prayer, napak pertiwi, and nyineb. The aim of creating this work and writing is to find the author's unique painting style inspired by pujawali activities using expressionist techniques. The method used in the process of creating this work of painting is the writing method by Hawkins, including the stages of exploration, improvisation and formation. The results of this activity correspond to the stages carried out, namely (1) in the exploration stage relevant ideas and studies related to the work created are produced; (2) the improvisation stage produces sketches in a sketchbook; and (3) the formation stage produced six works of painting according to the pujawali plot at Pura Dalem Tungkub Mengwitani.